2000
DOI: 10.1038/sj.ijo.0801425
|View full text |Cite
|
Sign up to set email alerts
|

Dietary intakes, eating style and overweight in the Stanislas Family Study

Abstract: OBJECTIVES: To describe the eating patterns of members of French families and to assess the relationships between dietary intakes, eating style and overweight. DESIGN: Cross-sectional analysis of nutritional and behavioural characteristics. SUBJECTS: 1320 members of 387 families (age 11 ± 65 y) attending the Centre for Preventive Medicine for a routine medical check-up. MEASUREMENTS: Individual body weight and height were measured. Food intake was assessed using a three day dietary record. Eating style was mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

32
116
4
9

Year Published

2007
2007
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(179 citation statements)
references
References 38 publications
32
116
4
9
Order By: Relevance
“…However, a consistent finding has been that associations between dietary restraint and body weight vary between obese and normal weight populations. In normal weight groups, the association is often positive, 38,39,42,43 whereas within obese populations higher restraint is usually associated with lower weight. [42][43][44][45] It may be that in normal weight populations restraint is acting as a marker for overeating tendencies, whereas in obese populations the overeating tendency is nearly ubiquitous, and in this group restraint will distinguish between those whose tendency to overeat is tempered by restraint and those who do not attempt to control their eating.…”
Section: Widely Used Methods Of Measuring Dietary Restraint Confound mentioning
confidence: 99%
“…However, a consistent finding has been that associations between dietary restraint and body weight vary between obese and normal weight populations. In normal weight groups, the association is often positive, 38,39,42,43 whereas within obese populations higher restraint is usually associated with lower weight. [42][43][44][45] It may be that in normal weight populations restraint is acting as a marker for overeating tendencies, whereas in obese populations the overeating tendency is nearly ubiquitous, and in this group restraint will distinguish between those whose tendency to overeat is tempered by restraint and those who do not attempt to control their eating.…”
Section: Widely Used Methods Of Measuring Dietary Restraint Confound mentioning
confidence: 99%
“…In addition, higher dietary restraint among adolescent females is associated with higher body weight but lower energy intake 51 . Higher dietary restraint in our study was associated with less fast food consumption and low quality snacking by the ninth grade.…”
Section: -Year Changes In Eating Behaviours Among Youthmentioning
confidence: 99%
“…In addition, earlier research suggests that the relationship between restraint eating behaviors depends on sample characteristics. Several studies found a positive cross-sectional association between restrained eating and BMI, 19,20 whereas others found no significant relationships 6,21 or inverse relationships. 22,23 In this investigation, we examine the relationship between restrained eating and BMI using participants with a range of BMI, as well as clinical and non-clinical samples.…”
Section: Introductionmentioning
confidence: 99%